Heutagogy: Implementation in civil employee competency development activities - Hailitik, Hengky Jemy; Kuswandi, Dedi (Journal of Research in Instructional, 2024)
In the contemporary educational era, the heutagogical approach, first introduced by Stewart Hase and Chris Kenyon, offers an innovative solution for self-determined learning. This research, using a literature study method, aims to discuss three primary aspects: the principles and design of the heutagogical approach, the development of civil employee competence, and the strategy for implementing the heutagogical approach in civil employee competence development. By examining articles and related publications, this study identifies how the principles and design of heutagogy can be integrated into the context of civil employee competence development. Furthermore, the research explores how digital technology can facilitate the heutagogical approach in civil employee competence development. The findings from the literature study indicate that the heutagogical approach holds significant potential in enhancing the effectiveness and efficiency of civil employee learning, especially when supported by appropriate digital learning resources. In conclusion, the heutagogical approach, provides a robust framework for civil employee competence development, enabling civil employee to remain relevant and adaptive amidst rapid changes in professional and technological demands.